The Fertility Rate in the EU Societies and Life Satisfaction of Contemporary Europeans - Prostak, Rafał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This is a common knowledge that demographic trends in the EU Member States does not ensure the substitutability of generations. Trying to explain the situation we usually point at cultural changes. Presuming that everyone looks for a meaningful life that brings satisfaction and sense we shall ask if contemporary European perceive parenthood as an important condition of that kind of life.
Keywords: fertility rate in the EU; life satisfaction; demographic crisis